PENGARUH TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS VII MTsN LUBUK BUAYA KOTA PADANG - Andria Catri Thamsin, Isesma Zurita, Harris Effendi Thahar, (Universitas Negeri Padang, 2017)
This article is written to find out the effect of copy the master technique toward the ability of writing procedure text by seventh grade students at MTsN Lubuk Buaya Kota Padang. The data of this research is the scores of the ability of writing procedure text. The data is collected by giving performance test of the ability of writing procedure text on samples before and after using copy the master technique. The ability of writing procedure text before and after using copy the master technique is compared to see the effect by using the formula of t-test. The result of the research show that (1) the ability of writing procedure text before using copy the master technique is on more than adequate qualification (LdC); (2) the ability of writing procedure text after using copy the master technique is on good qualification (B); and (3) based on t-test result, it is concluded that there is a significant effect between the using of copy the master technique toward the ability of writing procedure text by seventh grade students at MTsN Lubuk Buaya Kota Padang.Â Kata kunci: Â pengaruh, teknik copy the master, keterampilan menulis teks prosedurÂ